K.H. Hasyim Asy’ari’s view on Walāya (Sainthood) in Sufism - Nur Hadi Ihsan; Moh. Isom Mudin; Adib Fattah Suntoro (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
This paper examines K.H. Hasyim Asy'ari's concept of walāya (sainthood) by directly exploring his works such as Al-Durar al-Muntaṭirah fī Masā'il al-Tis'a 'Asharah, Ādāb Al-Ālim Wa Al-Muta’alim, and Tamyīz al-Haqq min al-Bāṭil. The reason for writing his books on Sufism is the phenomena of misunderstandings and deviations in the teachings of Sufism, especially among tarekat groups. This article is library-based research and the data are collected by applying documentary techniques; referring to books, journal articles, and other published materials. The data were then analyzed using the descriptive-analytical method. This study reveals that the concept of sainthood of K.H. Hasyim Asy’ari was influenced by the views of classical Sufis, among others, is al-Qusyairi. Generally, his understanding is similar to those of authoritative Sufis. According to him, walī is a person very close to God and he is protected from doing immoral acts. For that matter, a person who ignores the Shari'a (Islamic law) is not walī. In fact, a true walī will not reveal himself to be a walī, even if he knows.